Nanocarrier Breakthroughs: Revolutionizing Cancer Treatment with Nanotechnology - Patil, Vaibhav Lalchandra; Rane, Bhushan Rajendra; Jain, Ashish Suresh (Current Nanomaterials, 2025)
Cancer ranks as the second leading cause of death globally. Cancer can be addressed through several primary methods, including radiation therapy, chemotherapy, immunotherapy, surgery, or a combination of these treatments. Conventional cancer therapies often fall short due to several critical issues: they lack specificity, leading to damage in both cancerous and healthy cells; exhibit high cytotoxicity, causing severe side effects; have a short half-life, necessitating frequent administration; suffer from poor solubility, reducing effectiveness; encounter multi-drug resistance, diminishing their efficacy; and struggle with the presence of stem-like cancer cells, which can cause recurrence and metastasis. The development of nanotechnology has brought about a revolutionary phase in cancer therapy, and nanocarriers have emerged as a game-changing method of delivering medications. This paper explores the groundbreaking developments in using nanocarriers as a cancer treatment tool. This also covers the various research published in the last few years, multiple patents filed, ongoing and completed clinical studies, and FDA-approved nanocarriers. Nanocarriers, a diverse group comprising liposomes, polymeric nanoparticles, dendrimers, gold nanoparticles, carbon nanotubes, etc., present distinctive advantages in cancer therapy. These represent an improvement in cancer therapy tactics, including targeted drug delivery, controlled release kinetics, and the ability to overcome multidrug resistance mechanisms. The promise of these nanoscale vehicles in cancer is demonstrated by clinical achievements like those of Doxil, Abraxane, and Onivyde. These technologies will be improved by further research. Nanocarriers can effectively treat various cancers by the mechanism of active and passive targeting. The various applications of nanocarriers in diagnostic medicine, preventive medicine, and therapeutic medicine further improve their clinical applicability. Despite the vast amount of research being conducted in this area, several obstacles remain, including technological, biological, and regulatory challenges. Researchers are trying their best to find a way out of these difficulties. Further research on this topic will help to improve the clinical translation of nanocarriers.
Keywords: cancer therapy